(untitled) (Interdisciplinary Studies Journal, 2026)
This text consists of a thematic and theoretical excerpt of the so-called Didactic Objects (DO), extensionist concepts of the 6C/PCMA didactic sequence for teaching Natural Sciences. They are part of a doctoral research, and their proposal aims to fill gaps in the didactic sequences when applied in environments other than face-to-face, in other words, in blended (according to Brazilian nomenclature) or hybrid and virtual or distance learning. The article lists and defines two sets, those belonging (internal) and those not belonging (external) to the indicated sequence. Their didactic functionalities and applicability are explored, as well as the design of documents, models and guides for the implementation and elaboration of continuing education for educators, managers and researchers. References are presented for teaching approaches and strategies that can be added to the components described, since the objects also constitute connection interfaces between pedagogical instruments (planning, scripts, lesson plans) and technological instruments (educational management system).